Tisztesség, empátia, közgazdaságtan - Fazekas Károly (Hungarian Academy of Sciences, Institute of Economics, 2016)
– One of the basic premises of societies and economies is the capability of humans to understand and judge the aims and motivations of others. We are continuously observing the facial expressions of our fellows. We keep watching and try to understand the undercurrents of important events for us. While doing this, we strive for giving meaning to our experiences and try to fit them into familiar and formerly established patterns. There are three important phases of the process: empathy, understanding and judgment. Capabilities which are necessary to fulfill these tasks are important preconditions for successful competition and cooperation in the economy. Our capacity to empathize with the sentiments and deeds of the others is, however, a double-edged sword. It can induce both good-doings or harsh aggression for or against others. But, then, what is it that separates the good and the evil in humans? Lifesaving philanthropist or greedy martinet - man can be both. What is it that makes people helpful and forgiving individuals and why do they often emerge as revengeful destroyers? Can or should economic science deal with such types of inquiries? The purpose of this essay is to show that Adam Smith's insights relating to these questions provide us with thoughts which seem to be more and more relevant to contemporary scientific analysis.
Keywords: A13; B12; B31; B52; O10; 330; morality; economic growth; Adam Smith; empathy; institutions